Análise da eficiência energética de codificação de rede aplicada a redes cooperativas - Rayel, Ohara Kerusauskas (2013)
In this dissertation, an energy efficiency analysis of wireless systems is performed, comparing several schemes, from the direct transmission between two nodes, going through cooperative networks, where multiple nodes have independent information to send to a common destination, and getting to the most advanced network-coded cooperative systems. It is intended to evaluate the gain generated by the error rate reduction (caused by the network coding) and by the increase in the diversity order (provided by the cooperation between the nodes) in terms of the energy consumption reduction when transmitting the same amount of information. The analysis is performed considering Nakagami-m block fading, so the influence of some line-of-sight is also evaluated. Through the outage probability equations and a hardware model, energy consumption expressions for each scenario were obtained. Furthermore, through the graphical analysis of the numeric results, it was possible to notice that exists an optimal number of nodes that minimizes the energy consumption of the Generalized Dynamic Network Coding (GDNC) scheme for a given distance. An expression that represents this number was also obtained, and is the great contribution of this work, since if in the network project smaller sets containing the optimal number of nodes (called cooperation clusters) are organized, the energy consumption will be minimized. These results are also presented, and for the considered configuration, the energy saving can reach 10x.